2019
DOI: 10.1002/lno.11310
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mercury‐cycling genes in the Arctic and equatorial Pacific Oceans and their relationship to mercury speciation

Abstract: Humans are exposed to potentially harmful amounts of the neurotoxin monomethylmercury (MMHg) through consumption of marine fish and mammals. However, the pathways of MMHg production and bioaccumulation in the ocean remain elusive. In anaerobic environments, inorganic mercury (Hg) can be methylated to MMHg through an enzymatic pathway involving the hgcAB gene cluster. Recently, hgcA‐like genes have been discovered in oxygenated marine water, suggesting the hgcAB methylation pathway, or a close analog, may also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 72 publications
2
48
0
Order By: Relevance
“…Nevertheless, recent studies have shown that biological Hg II methylation is in most environments performed by a variety of microorganisms, carrying the hgcA and hgcB gene cluster (Gilmour et al , ; Parks et al ; Yu et al ). An increasing number of recent studies detailed below have intended to evaluate the biotic Hg II methylation by studying the biodiversity and activity of hgcAB + microorganisms (Gionfriddo et al ; Bravo et al , a ; Bowman et al ; Jones et al ; Villar et al ). Nevertheless, it is established that net MMHg production also depends on other concomitant processes, including (1) the composition and activity of the whole microbial community that in turn modulate the activity of hgcAB + microorganisms (Bravo et al ), (2) physico‐chemistry that controls Hg II bioavailability (Schaefer and Morel ; Jonsson et al ; Chiasson‐Gould et al ), and uptake in microorganisms (Schaefer et al ), and (3) biotic and abiotic MMHg demethylation (Du et al ).…”
Section: The Mercury Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, recent studies have shown that biological Hg II methylation is in most environments performed by a variety of microorganisms, carrying the hgcA and hgcB gene cluster (Gilmour et al , ; Parks et al ; Yu et al ). An increasing number of recent studies detailed below have intended to evaluate the biotic Hg II methylation by studying the biodiversity and activity of hgcAB + microorganisms (Gionfriddo et al ; Bravo et al , a ; Bowman et al ; Jones et al ; Villar et al ). Nevertheless, it is established that net MMHg production also depends on other concomitant processes, including (1) the composition and activity of the whole microbial community that in turn modulate the activity of hgcAB + microorganisms (Bravo et al ), (2) physico‐chemistry that controls Hg II bioavailability (Schaefer and Morel ; Jonsson et al ; Chiasson‐Gould et al ), and uptake in microorganisms (Schaefer et al ), and (3) biotic and abiotic MMHg demethylation (Du et al ).…”
Section: The Mercury Problemmentioning
confidence: 99%
“…A recent analysis of 243 seawater metagenome samples from 68 different sites of the Tara Oceans revealed high abundances of hgcAB corresponding to taxonomic relatives of known Hg II methylators from Deltaproteobacteria , Firmicutes , and Chloroflexi across all oceans, with the exception of the Arctic that was not studied (Villar et al ). More recently, Bowman et al (), combining PCR amplification and shotgun metagenomics, searched the hgcAB gene cluster in Arctic Ocean seawater without success. Out of all the hgcA ‐like genes found in the queries of marine metagenomes, the Nitrospina phylum, a marine nitrite oxidizing bacteria abundant in oxygen‐deficient zones, appeared to be widespread, predominant and likely a key player for MMHg production in the oxic subsurface waters of the global ocean (Villar et al ), including the Arctic (Bowman et al ) as well as Antarctic sea ice–brine–sea water interfaces (Gionfriddo et al ).…”
Section: Toward a Better Understanding Of Microbial Methylmercury Formentioning
confidence: 99%
“…Podar et al (2015) only 60 detected hgcAB genes in a few metagenomes from marine pelagic waters (seven out of 138 61 metagenomes) but highlighted that limited sequencing depths of these metagenomes could have 62 hampered detection. A more recent study did not detect hgcA genes in waters from the Arctic and 63 equatorial Pacific Oceans (Bowman et al, 2019). Interestingly, the presence of hgcAB-like genes 64 was reported in normoxic water from open ocean and sea ice in Antarctica, with a fraction of those 65 genes being associated to microaerophilic nitrite oxidizing bacteria (Gionfriddo et al, 2016;Villar 66 et al, 2020).…”
Section: Introduction 41mentioning
confidence: 95%
“…54 55 Recent advances in metagenomics have yielded new insights into the microbial taxonomic and 56 functional diversity in various aquatic ecosystems (e.g., Mehrshad et al, 2016;Haro-Moreno et al, 57 2018; Nowinski et al, 2019). The approach has for example been applied to broadly assess the 58 presence and diversity of genes central to biological Hg cycling in marine systems (Podar et al,59 2015; Gionfriddo et al, 2016;Bowman et al, 2019;Villar et al, 2020). Podar et al (2015) only 60 detected hgcAB genes in a few metagenomes from marine pelagic waters (seven out of 138 61 metagenomes) but highlighted that limited sequencing depths of these metagenomes could have 62 hampered detection.…”
Section: Introduction 41mentioning
confidence: 99%
“…In addition to the Hg-methylators confirmed in culture, sulfate-and iron-reducing Deltaproteobacteria, acetogenic and syntrophic Firmicutes, and methanogenic Archaea (Compeau and Bartha, 1985;Fleming et al, 2006;Kerin et al, 2006;Ranchou-Peyruse et al, 2009;Gilmour et al, 2013;Yu et al, 2013;Gilmour et al, 2018;Goñi-Urriza et al, 2019)genomic analyses have identified hgcAB (and thus inferred the ability to produce MeHg) in many other lineages including Chloroflexi, Chrysiogenetes, Aminicenantes (Candidate Phylum OP8), Atribacteria (Candidate Phylum OP9), Nitrospira, Nitrospina, Elusimicrobia, Thermotogae and Spirochaetes (Podar et al, 2015a;Gionfriddo et al, 2016;Liu et al, 2018a;Bowman et al, 2019;Christensen et al, 2019;Jones et al, 2019). The occurrence of hgcAB in Bacterial and Archaeal genomes is rare but widely dispersed across phyla (Parks et al, 2013;Podar et al, 2015a;Jones et al, 2019).…”
Section: Introductionmentioning
confidence: 99%